Gerakan Sadar Kesehatan Keselamatan Kerja di Rumah Kompos Padangtegal, Ubud Gianyar - Putu Nita Cahyawati; Ni Wayan Erly Sintya Dewi; Asri Lestarini; Pande Ayu Naya Kasih Permatananda; Anak Agung Sri Agung Aryastuti (Community Service Journal (CSJ), 2024)
Desa Padangtegal is one of the traditional villages in the Ubud area of Gianyar. Most of the village residents rely on the tourism sector for their livelihoods. Like other villages in Gianyar, tourism in this area also has negative environmental impacts, one of which is waste. Waste management activities have a relatively high risk of accidents and work-related diseases. Self-protection efforts and practices for clean and healthy living must always be implemented to minimize health impacts on this worker group. Based on the issues faced by the partners, the implementation team provided solutions in the form of occupational health and safety education and investment. To provide this education several stages were carried out, including preparation, implementation, monitoring, and evaluation. The partners present at this activity numbered 17 people. The partners involved work in transportation (47.06%), general duties (20.41%), and as drivers (17.65%). The majority of the partners are male (94.12%), aged 20-52 years, married (82.35%), and Hindu (100%). Most partners come from the Gianyar area (94.12%) and have worked between 2 to 11 years. The results of the pretest and posttest assessments showed an increase in knowledge among the partners, with pretest scores rising from 4.53 to 7.53. This activity concludes that it was carried out “Well”. This is assessed based on two indicators: the education activity effectively increased knowledge and the provision of investment. The pretest and posttest results show that knowledge nearly doubled from the initial score.